PREVALENCE OF ANEMIA IN CHILDREN 6 TO 59 MONTHS OF AGE IN GADAREF STATE, SUDAN -2013 - Dr. Mohmoud Mohammed Ahmed; Prof. Elsadig yousif Elbadawi (The Sky)
Background: Anemia is a condition characterized by reduction in thevolume of red blood cells and a decrease in the blood concentration of haemoglobin (less than 11gm/dl). Haemoglobin is a main part of red blood cells and binds oxygen. This can lead to range of adverse symptoms. The most common cause of anemia worldwide is an iron deficiency. This study attempted to estimate the prevalence of anemia among children 6 to 59 months of age in Gadaref State, and to determine the related factors, which include socio demographic factors and nutritional status of children.